Haemodynamic conditions of patient-specific carotid bifurcation based on ultrasound imaging - Luísa Costa Sousa (2014)
The purpose of this paper is to complement the characterisation of patient-specific carotid artery bifurcation haemodynamics based on image data obtained by Doppler ultrasound imaging. A methodology for patient-specific 3D luminal surface reconstruction followed by structured hexahedral meshing of the volume and blood flow simulation is presented. Quantitative descriptors of the flow based on wall shear stress (WSS) are used to compare healthy and stenosed carotid bifurcation haemodynamic disturbances. Independently on the presence of stenosis, the internal carotid artery has been identified as a region of abnormal high values of oscillating shear index and relative residence time and low values of time averaged WSS. For the healthy carotid bifurcation, WSS descriptors manage to capture flow disturbances at the external carotid artery. This work addresses the lack of quantitative analysis on anatomically realistic stenosed carotid bifurcations. (c) 2014 (c) 2014 Taylor & Francis.